Population Genomics and Phylogeography of a Clonal Bryophyte With Spatially Separated Sexes and Extreme Sex Ratios - Alonso-García, Marta; Villarreal A., Juan Carlos; McFarland, Kenneth; Goffinet, Bernard (Frontiers in Plant Science, 2020)
The Southern Appalachian (SA) is one of the most biodiversity‐rich areas in North America and has been considered a refugium for many disjunct plant species, from the last glacial period to the present. Our study focuses on the SA clonal hornwort, Nothoceros aenigmaticus J. C. Villarreal & K. D. McFarland. This hornwort was described from North Carolina and is widespread in the SA, growing on rocks near or submerged in streams in six and one watersheds of the Tennessee (TR) and Alabama (AR) Rivers, respectively. Males and female populations occur in different watersheds, except in the Little Tennessee (TN) River where an isolated male population exists ca. 48 km upstream from the female populations. The sex ratio of 1:0 seems extreme in each population. In this study, we use nuclear and organellar microsatellites from 250 individuals from six watersheds (seven populations) in the SA region and two populations from Mexico (23 individuals). We, then, selected 86 individuals from seven populations and used genotyping by sequencing to sample over 600 bi-allelic markers. Our results suggest that the SA N. aenigmaticus and Mexican plants are a nested within a clade of sexual tropical populations. In the US populations, we confirm an extreme sex ratio and only contiguous US watersheds share genotypes. The phylogenetic analysis of SNP data resolves four clusters: Mexican populations, male plants (Little Pigeon and Pigeon river watersheds) and two cluster of female plants; one from the Little Tennessee and Hiwassee Rivers (TR) and the other from the Ocoee (TR) and Coosa (AR) Rivers. All clusters are highly differentiated (Fst values over 0.9). In addition, our individual assignment analyses and PCAs reflect the phylogenetic results grouping the SA samples in three clades and recovering males and female plants have high genetic differentiation (Fst values between 0.5–0.9 using microsatellites and bi-allelic markers). Our results point to Pleistocene events shaping the biogeographical pattern seen in US populations. The extreme sex ratio reflects extreme isolation and highlights the high vulnerability of the populations in the SA.